Clinical predictors of low quality of life in patients with Parkinson’s disease - L. I. Kopylova; A. A. Tappakhov; T. Ya. Nikolaeva (Acta Biomedica Scientifica)
Background. Despite the comprehensive study of Parkinson’s disease (PD), studying the quality of life (QoL) of patients, especially the prediction of low QoL, remains an unresolved issue.The aim. To create a prognostic model for low quality of life in patients with Parkinson’s disease by studying the severity of clinical features.Materials and methods. The cross-sectional study included 104 patients diagnosed with PD (56 % of men, 48 % of women); the median age was 67.0 [60.0; 71.0] years; the median duration of the disease was 5.0 [2.0; 8.0] years. We assessed motor and non-motor symptoms of PD in all patients. The PDQ-39 (Parkinson’s Disease Questionnaire) scale was used to assess the patients’ QoL. We conventionally accepted a PDQ-39 score of 50 or more as a low QoL level in a patient. Binary logistic regression using the stepwise exclusion method was used to create a prognostic model for a low QoL level in a patient with PD.Results. To predict the probability of low QoL in patients with PD depending on the studied clinical manifestations, we proposed a function according to which female gender has the greatest impact on low QoL (odds ratio – 20.0; 95% confidence interval (95% CI): 1.82–222.26). An increase in the PD stage according to the Hoehn – Yahr scale by 1 unit causes 8.77 times increase (95% CI: 2.11–36.49) in the probability of low QoL, an increase on the Epworth sleepiness scale by 1 point – 2.33 times increase (95% CI: 1.24–4.38), an increase in the level of depression according to the HADS (Hospital Anxiety and Depression Scale) by 1 point – 1.93 times increase (95% CI: 1.13–3.32). The sensitivity and specificity of the obtained function were 95.9 and 80%, respectively.Conclusion. The proposed prognostic formula can be used in neurologists’ appointments to determine the probability of low quality of life in patients with Parkinson’s disease.